2019
DOI: 10.21203/rs.2.11999/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The predictive value of diaphragm ultrasound for weaning outcomes in critically ill children

Abstract: Background: Multiple studies have shown that diaphragmatic ultrasound can better predict the outcome of weaning in adults. However, there are few studies focusing on children, leading to a lack of sufficient clinical evidence for the application of diaphragmatic ultrasound in children. The purpose of this study is to investigate the predictive value of diaphragm ultrasound for weaning outcomes in critically ill children. Methods: The study included 50 cases whose mechanical ventilation (MV) time was >48 h, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…We could not find any difference in pre‐extubation DTF in children with successful extubation from failed extubation. Previously, a study in children reported DTF ≥ 21% as a predictor of successful extubation 4 . But a large multicentric adult study found no association of pre‐extubation DTF with extubation outcome 25 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We could not find any difference in pre‐extubation DTF in children with successful extubation from failed extubation. Previously, a study in children reported DTF ≥ 21% as a predictor of successful extubation 4 . But a large multicentric adult study found no association of pre‐extubation DTF with extubation outcome 25 .…”
Section: Discussionmentioning
confidence: 97%
“…In patients requiring thoracic surgery, muscle biopsies of the diaphragm and latissimus dorsi demonstrated a 35% reduction in force‐generating capacity of the diaphragm within 2 h of surgery but not latissimus dorsi 3 . Diaphragm being the major respiratory drive muscle, VIDD has an adverse impact on weaning off and is associated with prolonged mechanical ventilation and hospital stay 4 . Conventional measures of diaphragmatic function such as phrenic nerve conduction study, transdiaphragmatic pressure measurement, pulmonary function testing, fluoroscopy, and diaphragmatic electrical activity, have limitations such as the need for special equipment, invasiveness, and exposure to ionizing radiations 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we compensated for this by obtaining our Mmode measures over the most moving point of the hemidiaphragm on B-mode. Moreover, M-mode technique has been successfully used in previous studies to measure diaphragmatic thickness in excursion in adults and pediatric age groups [9,30]. A potential technical limitation to our study is the use of a micro-convex transducer rather than a high-frequency microlinear transducer for imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The second cause may be that majority of adult patients suffered from chronic obstructive pulmonary disorder (COPD), where muscle fibers of the diaphragm undergo chronic oxidative remodeling, resulting in weakness in the ability of diaphragm compensation [26]. Third, the average time for ventilatory treatment was more the elderly than that in the children with DD [576 (374-850) hrs vs 360 (168-528)] [6,22]. In addition, in critically ill children, we observed that the time of ventilation is a risk factor independent of DD, similar to that observed in adult studies [2,27].…”
Section: Discussionmentioning
confidence: 99%